System Dynamics Simulation Model to Increase Paddy Production for Food Security - Mala Rosa Aprillya; Erma Suryani; Anisa Dzulkarnain (Journal of Information Systems Engineering and Business Intelligence, 2019)
Background: Food security is a world problem that often affects developing countries, one of them in Indonesia. Along with the increasing population growth population in Indonesia, this will affect the level of demand for rice for food needs. The problem of rice consumption and its fulfillment is an important agenda. If Indonesia does not want to depend on rice imports, then paddy production must continue to be increased. Therefore, food availability in each region is maintained to realize food security. Objective: The purpose of this study is to analyze the factors that influence the increase paddy production in terms of cultivation and postharvest using a system dynamics model approach as the basis for policy strategy preparation.Methods: System Dynamics (SD) approach with the consideration that this framework offers the ability to study and manage complex feedback systems and the ability to model non-linear behavior. Then do a series of decision scenarios to get the best results using computer assistance.Results: Scenario results indicate that increasing paddy production to meet demand in Indonesia can be done by increasing the adoption of postharvest harvesting mechanisms coupled with the application of appropriate GAP (Good Agricultural Practice). It will increase paddy production in East Java so that it will make a large contribution to rice production in East Java.Conclusion: This research can be used to improve paddy production to food security by improving harvesting mechanisms. For further research, we can consider increasing rendement paddy in supporting increased rice production.